2012
DOI: 10.1124/dmd.112.048678
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Differential Cocaine Metabolism in Mouse and Rat through Metabolomics-Guided Metabolite Profiling

Abstract: Rodent animal models have been widely used for studying neurologic and toxicological events associated with cocaine abuse. It is known that the mouse is more susceptible to cocaine-induced hepatotoxicity (CIH) than the rat. However, the causes behind this species-dependent sensitivity to cocaine have not been elucidated. In this study, cocaine metabolism in the mouse and rat was characterized through LC-MS-based metabolomic analysis of urine samples and were further compared through calculating the relative ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Samples of the polar lipophilic DNPH adducts from FF were collected between 32 and 33 min from the HPLC column corresponding to the retention times of pure HNE-DNPH, and the pooled samples were subjected to LC/MS analysis. This analysis was completed by a previously published technique [33]. A 5 µL aliquot of the pooled samples was injected into a Waters Acquity ultra-performance liquid chromatography system (Milford, MA) and separated by a gradient of mobile phase ranging from water to 95 % aqueous acetonitrile containing 0.1 % formic acid over a 10 min run.…”
Section: Liquid Chromatography-mass Spectroscopy (Lc/ms) Analysis Of mentioning
confidence: 99%
“…Samples of the polar lipophilic DNPH adducts from FF were collected between 32 and 33 min from the HPLC column corresponding to the retention times of pure HNE-DNPH, and the pooled samples were subjected to LC/MS analysis. This analysis was completed by a previously published technique [33]. A 5 µL aliquot of the pooled samples was injected into a Waters Acquity ultra-performance liquid chromatography system (Milford, MA) and separated by a gradient of mobile phase ranging from water to 95 % aqueous acetonitrile containing 0.1 % formic acid over a 10 min run.…”
Section: Liquid Chromatography-mass Spectroscopy (Lc/ms) Analysis Of mentioning
confidence: 99%
“…However, as has been noted in other studies, xenobiotic metabolism can vary both qualitatively and quantitatively between species (Kanamori et al, 2011;Roberts et al, 1991), suggesting caution when drawing conclusions based on cross-species assays. Species-dependent differences in COC metabolite profiles were recently examined by Yao et al, demonstrating not only quantitative and qualitative shifts in metabolism but also suggesting that the primary route of oxidative COC metabolism may differ between species (Yao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed how the metabolic phenotype of animal disease models for osteoarthritis and multiple sclerosis overlapped with the patients' metabolic phenotype, indicating the potential of metabolomics for interspecies translation [71,72,86,87]. Although no efforts have yet been made to compare the animal and human metabolic phenotypes after drug treatment in vivo, the rat and mouse metabolic phenotypes were compared to study their differential sensitivity to cocaine [88]. It was found that the aryl hydroxylation pathway was dominant in rats, causing increased excretion of cocaine, which was not the case in mice.…”
Section: Translational Pharmacometabolomics To Study Cns Drug Effectsmentioning
confidence: 99%